Respuesta :
Answer:
[tex]x=\frac{27+\sqrt143i}{8}{} ,\frac{27-\sqrt{143i} }{8}[/tex]
[tex]y=-9+\frac{27+\sqrt{143} i}{4} ,-9+\frac{27-\sqrt{143} i}{4}[/tex]
Step-by-step explanation:
1) Solve for 2x - y = 9
A. Solve for y.
2x - y = 9
B. Subtract 2x from both sides.
-y = 9 - 2x
C. Multiply both sides by -1.
y = -9 + 2x
D. Regroup terms.
y = 2x - 9
2) Substitute y = 2x- 9 into 4x² + 3y² - 2x + y = 16
A. Start with the original equation.
4x² + 3y² - 2x + y = 16
B. Let y = 2x - 9.
4x² + 3(2x - 9)² - 2x + 2x - 9 = 16
C. Simplify.
16x² - 108x + 234 = 16
3) Solve for x in 16x² - 108x + 234 = 16
A. Solve for x.
16x² - 108x + 234 -= 16
B. Move all terms to one side.
16x² - 108x + 234 - 16 = 0
C. Simplify 16x² - 108x + 234 - 16 to 16 x² - 108x + 218
16 x² - 108x + 218 = 0
D. Use the Quadratic Formula.
[tex]x=\frac{108+4\sqrt{143}i }{32}[/tex], [tex]\frac{108-4\sqrt{143} i}{32}[/tex]
E. Simplify solutions.
[tex]x=\frac{27+\sqrt{143} i}{8} ,\frac{27-\sqrt{143} i}{8}[/tex]
4) Substitute [tex]x=\frac{27+\sqrt{143}i }{8} ,\frac{27-\sqrt{143}i }{8}[/tex] into y = 2x - 9.
1) Start with the original equation.
y = 2x - 9
2) Let x = [tex]\frac{27+\sqrt{143} i}{8} ,\frac{27-\sqrt{143}i }{8} .[/tex]
[tex]y=2*\frac{27+\sqrt{143} i}{8} -9,2*\frac{27-\sqrt{143}i }{8} -9[/tex]
3) Simplify
[tex]y=-9+\frac{27+\sqrt{143}i }{4} ,-9+\frac{27-\sqrt{143i} }{4}[/tex]